Effects of supplier orientation and competitive strategies on ICT firms' performance - Çelikyay, Mehmet; Sönmez Çakır, Fatma; Adıgüzel, Zafer (Emerald Publishing, 2023)
Purpose The purpose of this study is to investigate the relationship between supplier orientation, which is Porter's general competitive strategy, and the market and financial performance in the Turkish Information and Communication Technologies (ICTs) sector, taking into account the problems in the supply chain during the pandemic process. Design/methodology/approach This study used a quantitative research design where 550 questionnaires were collected from respondents operating in various ICT companies in Turkey to obtain necessary data to test the hypotheses developed for the study. Mediation effect and path analysis were used to analyze the research data. Smart PLS 3.3 version was used for all the mentioned analyzes. Findings The results of the analysis revealed that supplier orientation was positively and significantly related to financial and market performance. The findings of this study also showed that Porter's generic competitive strategies have a mediator role in the relations of supplier orientation, financial and market performance. Practical implications These findings contribute to the understanding of the importance of supplier orientation along with competitive strategies to increase market and financial performance in ICT companies, especially during the pandemic process. These findings provide recommendations for researchers, professionals and senior and supply chain managers to apply at their firms. Originality/value This is a study that adequately covers the relationship between supplier orientation, general competitive strategies and market and financial performance in the Turkish ICT sector, taking into account the pandemic process.
Keywords: Supplier Orientation; Competitive Strategies; Market Performance; Financial Performance; SmartPLS